É arte ou é verdade: arte e ciência sob a luz das filosofias de Nelson Goodman e Bertrand Russell - Holanda, Euclícia Queiroz de (2025)
Are there similarities between art and science? What relationship can we draw between them? Are they sources of knowledge and instruments for constructing the world? Nelson Goodman would say yes. The philosopher states, in his theory of symbols, that art and science are similar when we think of both as sources of knowledge of things. For him, there is a relationship of continuity between them, since both are symbolic systems, through which we can understand and construct reality. With this, Goodman does not want to invalidate any scientific knowledge, but to bring what emotions, creativity and irrationality offer us, in order to expand our cognition. Art and science are, therefore, capable of constructing different worlds, or different versions of worlds, as Goodman states. Art and science are, therefore, capable of constructing different worlds, or, in Goodman's words, different versions of the world. My goal is to show whether art has a role in epistemology, whether it, in addition to being a form of expression, communication and access to the world, is also a way of knowing and constructing other realities. To this end, we will first analyze the concepts of “truth” and “knowledge,” then explain the theory of symbols. The next step is to analyze the concept of science and how it works today. Once this is done, we will analyze whether art and science can be equivalent in the context of general knowledge of things.